Cerebral Infarction in a Child after Moderate Brain Trauma: A Case Report - Gohil, Dhaval; Devi, Bhagavatula Indira; Bhat, Dhananjaya I.; Shukla, Dhaval (Indian Journal of Neurotrauma, 2017)
Intracranial hematomas and contusions are common entity after traumatic brain injury in children and young population. However, cerebral infarction after traumatic head injury is a rare entity with frequency ranging from 1.9 to 10.4%. We herein report a case of cerebral infarction in right anterior cerebral artery (ACA) and parts of middle cerebral artery (MCA) territory after moderate head injury in a 14-year-old boy, in whom computed tomographic (CT) scan of the brain was performed 3.5 hours after injury, which showed specks of pneumocephalus in sellar suprasellar region, and 12 hours after injury showed right ACA territory infarct and evolving infarct in right MCA territory. Bony injury included right orbital roof and right sphenoid wing linear undisplaced fractures. Possible mechanism for development of infarction is right internal carotid artery (ICA) dissection by fractured bone fragments and/or thrombosis. The patient developed hemiplegia on second day after trauma. Intracranial pressure (ICP) monitoring was done, which was suggestive of raised ICP. The patient underwent right fronto-temporo-parieto craniotomy and decompression (tissue sent for histopathologic analysis) and augmentative duraplasty with bone flap replacement on fifth day after trauma. Histopathology was suggestive of cerebral infarct with hemorrhage. The patient was improved at follow-up, 10 months after trauma after rehabilitation, and physiotherapy to modified Rankin scale (mRS) score 3. Hence delayed CT scan plays a vital role in detecting developing posttraumatic infarcts, and rigorous rehabilitation care is necessary for clinical improvement.
Keywords: infarct; traumatic; computed tomographic scan; modified Rankin scale; rehabilitation